CORRELATION OF PRIMARY DISEASE CASES WITH BASIC SANITATION IN THE MUNICIPALITY OF ANÁPOLIS, GOIÁS - Souza, Daniel Morais; Boggione, Giovanni de Araújo (CIPEEX, 2025)
This paper presents the ‘State of the Art’ scheduled for the preparation of a Master's Dissertation currently being developed in the Stricto Sensu Postgraduate Programme in Environmental Sciences at the Evangelical University of Goiás (UniEVANGÉLICA). The study explores the relationship between the incidence of primary diseases and the lack of or inadequate provision of basic sanitation services in the municipality of Anápolis, highlighting the impacts on public health and possible mitigation measures. For basic sanitation, access to drinking water services, sewage collection and treatment, solid waste management, and urban drainage were considered in association with the occurrence or prevention of diseases such as diarrhea, hepatitis A, cholera, schistosomiasis, and leptospirosis. Addressed in the dissertation, the work includes the provision of. The dissertation analyzes existing public policies and health education programs implemented to reduce hospital admissions due to lack of basic sanitation, proposing recommendations for the development of future research to be carried out. A deductive approach was used to support the study and due to the relevance of the topic, with documentary analysis and bibliographic review procedures. However, in order to ensure the reliability of the statistical data, secondary sources available on government health and sanitation websites were used, as well as the possible investments that have been made to universalize access to sanitation and the costs of consultations and hospitalizations in the municipality of this research, enabling the Research Project that will serve as the basis for writing the Final Paper of the Program.